KONSUMSI AIR MINUM DAN KARIES GIGI PADA ANAK SEKOLAH DASAR DI KABUPATEN BANJAR - Rasuna Ulfah (Poltekkes Kemenkes Banjarmasin, 2022)
According to WHO data, 60-90% of school children throughout the world experience dental caries. Factors that influence dental caries are the physical environment, namely water as a source of daily drinking water. Consuming drinking water with a low pH will increase the risk of dental caries. This study aims to find out the description of the pH of drinking water and dental caries in elementary school children in Banjar Regency. This type of research is descriptive research. The population in this study were all elementary school students in the Banjar Regency area. The sampling technique in this research is multistage cluster sampling. Calculation of sample size using hypotheses for two population proportions. The samples taken in this research were 136 students in grades I, II and III of elementary school. The results of the data obtained will be presented descriptively in the form of frequency distribution and percentage. The research results showed that the pH of the drinking water consumed by respondents was 82.4% normal, and 82.4% had high dental caries. The conclusion from this study was that the pH of the drinking water consumed by respondents was at normal pH and respondents experienced high levels of dental caries. Respondents were advised to maintain healthy teeth by reducing consumption of sweet and sticky foods and brushing their teeth in the right way and at the right time